A new four‐step method to identify the parameters of transmission line based on SCADA data. Issue 9 (11th February 2022) - Kong, He; Lu, Min; Que, Lingyan; Xu, Feiyang; Zhao, Junbo; Xue, Ancheng
Abstract: Accurate parameters of transmission line (ParTL) are the basis of power system analysis. For high‐voltage transmission line (TL), remote terminal units (RTUs) are widely installed to provide supervisory control and data acquisition (SCADA) measurements. Based on multiple snapshots of SCADA data at both ends of the TL, a four‐step method to identify ParTL is proposed in this paper. In detail, based on the π‐model of TL, the relationship between voltage phase angle difference (VPADs) and parameter identification is presented. And then, the general estimation formulation for VPADs is established. Furthermore, four steps to simplify and solve the formulation are detailed, that is, firstly after the approximated relationship between VPADs and reactance are derived, the estimation of VPADs at multiple snapshots is converted into the optimal problem with reactance of TL, just one variable, and the VPADs are estimated roughly; secondly based on the median estimation, the ParTL are identified roughly; thirdly, combined with Taylor series expansions and the alternating current power flow model, the VPADs are estimated accurately; fourthly, the ParTL are identified accurately. Finally, the results with simulated and field data verify the effectiveness and practicality of the proposed method.